Atuty logistyczne i marketingowe oferty turystycznej on-line - Dąbrowska, Barbara (Advantages of Logistic and Marketing Tourist Offer on line, 2005)
This article presents advantages of using technologies on line for making tourist offer. The author shows features of promotion and distribution; costs of e-marketing. Logistic advantages of tourist offer may be bigger. A reengineering of tourist processes is necessary.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 189-194